2020
DOI: 10.1136/bmjmilitary-2020-001591
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide epidemiology of foot and ankle injuries during military training: a systematic review

Abstract: IntroductionMusculoskeletal foot and ankle injuries are commonly experienced by soldiers during military training. We performed a systematic review to assess epidemiological patterns of foot and ankle injuries occurring during military training.MethodsA review of the literature was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The search, done on 14 February 2019, resulted in 1603 reports on PubMed, 565 on Embase and 3 on the Cochrane Library. After r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 97 publications
1
1
0
Order By: Relevance
“…Descriptive data from the MSP questionnaire showed that MSDs were most common in the low back, knee, lower leg, and foot. These data are in line with international reports 3 , 6 , 17 , 34 and corroborate previous findings of the 1-year and point prevalence of MSDs in male conscripts, 23 military personnel, 25 and male deployed soldiers 28 in the SwAF. In accordance with previous research, 28 the median intensity ratings were at the lower end.…”
Section: Discussionsupporting
confidence: 92%
“…Descriptive data from the MSP questionnaire showed that MSDs were most common in the low back, knee, lower leg, and foot. These data are in line with international reports 3 , 6 , 17 , 34 and corroborate previous findings of the 1-year and point prevalence of MSDs in male conscripts, 23 military personnel, 25 and male deployed soldiers 28 in the SwAF. In accordance with previous research, 28 the median intensity ratings were at the lower end.…”
Section: Discussionsupporting
confidence: 92%
“…Musculoskeletal injuries (MSK-I) in military service members are a significant problem worldwide, [1][2][3][4][5] adversely impacting work, combat readiness and national security. 6 In the USA and the UK, MSK-I are the leading cause for seeking medical care 1 and discharge from military service.…”
Section: Introductionmentioning
confidence: 99%